Extracellular biosynthesis of biocompatible CdSe quantum dots. Issue 9 (25th September 2019) - Xu, Jie; Hu, Ruiqing; Wang, Qiuhan; Wang, Ping; Bao, Haifeng
Abstract : An extracellular biosynthesis method has been developed to prepare cadmium selenide (CdSe) quantum dots (QDs) with strong fluorescence emission by incubating cheap Cd and Se inorganic salts with Escherichia coli ( E.coli ) bacteria. Ultraviolet–visible absorption spectra, photoluminescence (PL) spectra, and high‐resolution transmission electron microscopy analysis showed that the biosynthesised CdSe QDs have an average size of 3.1 nm, the excellent optical properties with fluorescence emission around 494 nm, and the good crystallinity. It was found that addition of 80 mg of mercaptosuccinic acid resulted in the formation of CdSe QDs with highest PL intensity. Furthermore, Fourier‐transform infrared spectra of as‐synthesised CdSe QDs confirmed the presence of a surface protein capping layer. The biosynthesised CdSe QDs were incorporated into the yeast cells as illustrated by laser confocal scanning microscopy images, showing a great potential in bio‐imaging and bio‐labelling application.